2011
DOI: 10.1007/s12028-011-9620-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Neurointensivist on Outcomes in Critically Ill Stroke Patients

Abstract: Introduction Current guidelines for management of critically ill stroke patients suggest that treatment in a neurocritical care unit (NCCU) and/or by a neurointensivist (NI) may be beneficial, but the contribution of each to outcome is unknown. The relative impact of a NCCU vs. NI on short- and long-term outcomes in patients with acute ischemic stroke (AIS), intracerebral hemorrhage (ICH) and aneurysmal subarachnoid hemorrhage (SAH) was assessed. Methods 2,096 stroke patients admitted to a NCCU or non-neuro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
54
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 14 publications
4
54
0
2
Order By: Relevance
“…Should one therefore conclude from this study that there is no benefit to be gained from specialist intensive care in the management of SE, in contrast to what has been demonstrated in other acute neurological pathologies [4,5]?…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Should one therefore conclude from this study that there is no benefit to be gained from specialist intensive care in the management of SE, in contrast to what has been demonstrated in other acute neurological pathologies [4,5]?…”
mentioning
confidence: 66%
“…Regarding the management modalities, the only significant difference related to continuous EEG monitoring, performed in 85 % of cases in NICU compared to 30 % in MICU. The higher rate of intubation in MICU (72 %, compared to 48 % in NICU) was partially correlated with consciousness impairment.Should one therefore conclude from this study that there is no benefit to be gained from specialist intensive care in the management of SE, in contrast to what has been demonstrated in other acute neurological pathologies [4,5]?We are convinced that some SEs may benefit from a neurological ICU, even if the study of Varelas et al failed …”
mentioning
confidence: 72%
“…Knopf [2012] studied 2,096 AIS patients and found that those treated in an NICU or by a neurologic critical care specialist had lower in-hospital mortality, better discharge disposition, and shorter hospital LOS compared to controls. [17].…”
Section: Fig 3 Total Icu and Hospital Stay Days For Extubated And Tmentioning
confidence: 99%
“…Knopf [2012] studied 2,096 AIS patients and found that those treated in an NICU or by a neurologic critical care specialist had lower in-hospital mortality, better discharge disposition, and shorter hospital LOS compared to controls. [17]. Similarly, Varelas [2008] performed a prospective analysis of 433 AIS patients, 259 of which were admitted after a NCC service had been put in place.…”
Section: Fig 3 Total Icu and Hospital Stay Days For Extubated And Tmentioning
confidence: 99%
“…A growing body of literature supports that patients with traumatic brain injuries, 6 ischemic strokes, 7 intracerebral hemorrhages, 8 and subarachnoid hemorrhages 9 all have better outcomes and shorter hospital stay when treated by physicians with neurocritical care training. In an effort to disseminate the knowledge of basic neurocritical care competencies, the Neurocritical Care Society developed the Emergency Neurological Life Support course, with the same guiding principles of the Advanced Cardiac Life Support training.…”
mentioning
confidence: 99%